Location, location, location: environmental factors better predict malaria-positive individuals during reactive case detection than index case demographics in Southern Province, Zambia. (December 2017) - Larsen, David; Ngwenya-Kangombe, Tokozile; Cheelo, Sanford; Hamainza, Busiku; Miller, John; Winters, Anna; Bridges, Daniel
Abstract Background Decreasing malaria transmission leads to increasing heterogeneity with increased risk in both hot spots (locations) and hot pops (certain demographics). In Southern Province, Zambia, reactive case detection has formed a part of malaria surveillance and elimination efforts since 2011. Various factors may be associated with finding malaria infections during case investigations, including the demographics of the incident case and environmental characteristics of the location of the incident case. Methods Community health worker registries were used to determine what factors were associated with finding a malaria infection during reactive case detection. Results Location was a more powerful predictor of finding malaria infections during case investigations than the demographics of the incident case. After accounting for environmental characteristics, no demographics around the incident case were associated with finding malaria infections during case investigations. Various time-invariant measures of the environment, such as median enhanced vegetation index, the topographic position index, the convergence index, and the topographical wetness index, were all associated as expected with increased probability of finding a malaria infection during case investigations. Conclusions These results suggest that targeting the locations highly at risk of malaria transmission is of importance in elimination settings.